Fork-tip needle biopsy versus fine-needle aspiration in endoscopic ultrasound-guided sampling of solid pancreatic masses: a randomized crossover study - Oppong, Kofi W.; Bekkali, Noor L. H.; Leeds, John S.; Johnson, Sarah J.; Nayar, Manu K.; Darné, Antony; Egan, Mark; Bassett, Paul; Haugk, Beate (Endoscopy, 2020)
Background A novel fork-tip fine-needle biopsy (FNB) needle has recently been introduced for endoscopic ultrasound (EUS)-guided sampling. The aim of this study was to compare the performance of fork-tip FNB histology and standard fine-needle aspiration (FNA) cytology in the diagnosis of solid pancreatic masses.Methods A randomized crossover study was performed in patients referred for EUS-guided sampling. Three passes were taken with each needle in a randomized order. Only samples reported as diagnostic of malignancy were considered positive. The primary end point was the sensitivity of diagnosis of malignancy. Secondary end points included the amount of sample obtained, ease of diagnosis, duration of tissue sampling, pathologist viewing time, and cost.Results 108 patients were recruited. Median age was 69 years (range 30 – 87) and 57 were male; 85.2 % had a final diagnosis of malignancy. There were statistically significant differences in sensitivity (82 % [95 % confidence interval (CI) 72 % to 89 %] vs. 71 % [95 %CI 60 % to 80 %]), accuracy (84 % [95 %CI 76 % to 91 %] vs. 75 % [95 %CI 66 % to 83 %]), proportion graded as a straightforward diagnosis (69 % [95 %CI 60 % to 78 %] vs. 51 % [95 %CI 41 % to 61 %]), and median pathology viewing time (188 vs. 332 seconds) (P < 0.001) between FNB and FNA needles, respectively. There was no significant difference in cost between an FNB or FNA strategy.Conclusion The diagnostic performance of the fork-tip FNB needle was significantly better than that of FNA; it was associated with ease of diagnosis, shorter pathological viewing times, and was cost neutral.